Investigation on Rice Husk Combustion in a Fluidized Bed with Longitudinal Vortex Generators - Smith Eiamsa-ard; Khwanchit Wongcharee; Suriya Chokphoemphun; Varesa Chuwattanakul; Pongjet Promvonge (My University, 2019)
Effects of wavy-ribbed surface chamber on combustion temperature/efficiency and exhaust gas behaviours in a fluidized bed combustor were investigated. In the experiments, the five wavy-rib pairs were placed at the bottom chamber for inducing longitudinal vortex flow which enhanced the fuel and fluid/combustion-air mixing in the top chamber for giving better combustion efficiency. The experiments were examined at five percent excess airs of EA = 15%, 30%, 45%, 60%, and 75% and were tested at the constant air mass flow rate of 95 kg/hr. From experimental results, it can be showed that a fluidized bed combustor with wavy-ribbed surface chamber can be promoted the high combustion efficient for all test runs especially at the percent excess airs of EA = 75%.
Keywords: Fluidized bed combustion; Secondary air injection; Combustion and flame dynamics